PARTISIPASI MASYARAKAT DAN EFEKTIVITAS PELAKSANAAN PROGRAM (PTSL) DI DESA RINGINPITU, KEC. PLEMAHAN, KAB. KEDIRI - Alvidianto, Manggala Bagus (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The problems raised in this study are (1) What is the role/participation of the community in optimizing the implementation of the PTSL program properly? (2) How is the effectiveness of the PTSL program in Ringinpitu Village? This study uses descriptive qualitative research using interview survey methods, and qualitative methods. Researchers also use source triangulation. Sources of data were obtained by interviewing informants. The results of this study show that the participation of the Ringinpitu village community is quite active, which can be proven when I conducted interviews with several informants who stated that the community was very enthusiastic about welcoming the PTSL program. The PTSL program that took place in Ringinpitu village was considered effective despite being constrained by the COVID-19 pandemic.